לפתור עבור b בנוסחה 3a + 2b = c? A.b = -3a + c B.b = c-2 / 3a C.b = -3a + c / 2 db = 2c / 3a

לפתור עבור b בנוסחה 3a + 2b = c? A.b = -3a + c B.b = c-2 / 3a C.b = -3a + c / 2 db = 2c / 3a
Anonim

תשובה:

# b = c / 2-3 / 2a #

הסבר:

הפחתה # 3a #:

# 2b = c-3a #

חלוקת #2#

# b = c / 2-3 / 2a #

תשובה:

# b = (c-3a) / 2 to (b) #

הסבר:

# "לבודד" 2b "על ידי חיסור" 3a "משני הצדדים"

#cancel (3a) ביטול (-3a) + 2b = c-3a #

# 2b = c-3a #

# "מחלק את שני הצדדים על ידי 2" #

# (ביטול (2) b) / ביטול (2) = (c-3a) / 2 #

# b = (c-3a) / 2 = (3a + c) / 2 to (b) #